A motorized cutter - Misron, Norhisam; Raja Othman, Raja Nor Firdaus; Rizuan, Suhairi; Jelani, Abdul Razak (2011)
The present invention is about an apparatus that has a gear and transmission system that converts rotational force to linear force driven by an electrical motor. An electrical motor is proposed to replace the ineffective shaft inside the pole. The electrical motor will produce rotational motion that connected to gears. These gears is designed to increased the torque that produced by the motor to certain value of ratio. The con-rod in the gear system converts the rotational motion to linear motion which will activate the sickle system to move up-down in its longitudinal direction, thus performing the cutting force. The system consists of four main components which are electrical motor, gears system and sickle system.